2022
DOI: 10.1039/d1dt04222j
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate metal–organic framework MTV-MIL-101 via post-synthetic cation exchange: is it truly achievable?

Abstract: Applying Szilágyi's procedure for the SACS process using aqueous solutions resulted in the formation of the metal oxide particles. However, by using DMF, mixed-metal MIL-101 was successfully obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The π–π electron transition in terephthalic acid is accountable for the absorption at 400 nm, while the d‐d electron transfer between trimers is accountable for the absorption at 600 nm. [ 41 ] Because PANI has superior light absorption, the absorptions of PANI@MIL‐101(Cr) and PANI@MIL‐101(Cr)@CeO 2 are significantly enhanced. For MIL‐101(Cr)@CeO 2 , its absorption peak slightly shifts, suggesting that electrons are more prone to transitions.…”
Section: Resultsmentioning
confidence: 99%
“…The π–π electron transition in terephthalic acid is accountable for the absorption at 400 nm, while the d‐d electron transfer between trimers is accountable for the absorption at 600 nm. [ 41 ] Because PANI has superior light absorption, the absorptions of PANI@MIL‐101(Cr) and PANI@MIL‐101(Cr)@CeO 2 are significantly enhanced. For MIL‐101(Cr)@CeO 2 , its absorption peak slightly shifts, suggesting that electrons are more prone to transitions.…”
Section: Resultsmentioning
confidence: 99%
“…22,25 Liu et al 22 and Zhao et al 25 found that the BET surface area of MIL-101 (Fe) is 608 m 2 g −1 and 199 m 2 g −1 , respectively. Zorainy et al 32 The texture properties and the crystal size of MIL-101 (Fe) are signicantly inuenced by the synthesis conditions. 21 In comparison to MIL-101 (Fe), the BET surface area, the total pore volume and the micropore volume decreased dramatically (Table 2), which can be ascribed to the coverage of MIL-101 (Fe) by nonporous GO sheets with low surface area.…”
Section: Gas Permeation Measurementsmentioning
confidence: 99%
“…Liu et al22 and Zhao et al25 found that the BET surface area of MIL-101 (Fe) is 608 m 2 g −1 and 199 m 2 g −1 , respectively. Zorainy et al32 found the BET surface area of MIL-101 (Cr) and mixed-metal MIL-101(Cr/Fe) is over 2000 m 2 g −1 . Comparing with MIL-101 (Cr), the low BET surface area of the synthesized MIL-101 (Fe) could be attributed to the smaller crystal size of MIL-101 (Cr) than the synthesized MIL-101 (Fe).The texture properties and the crystal size of MIL-101 (Fe) are signicantly inuenced by the synthesis conditions 21.…”
mentioning
confidence: 99%
“…Post-synthetic exchange (PSE) of building blocks in metal–organic frameworks (MOFs) is a well-established and effective method for creating multivariate MOFs (MTV-MOFs). These MTV-MOFs display improved properties that go beyond the mere sum of their individual components. Despite the common occurrence of PSE, the details of the exchange process remain not fully understood. When the diffusion rate of the incoming building blocks is slower than their exchange rate, a surface-to-core directional exchange takes place. This results in a heterogeneous microstructural MTV-MOF, which, during the PSE process, displays a three-dimensional (3D) core–shell distribution of original and incoming building blocks.…”
Section: Introductionmentioning
confidence: 99%